Management of vaccination - related anaphylaxis - Ariyanto Harsono (Paediatrica Indonesiana, 2001)
Anaphylaxis is a systemic, immediate hypersensitivity reaction due to IgE mediated immunologic release ofmediators from mast cells and basophils. Features of severe condition are obstruction of the upper airway from tissueswelling, marked bronchospasm, and hypotension. In vaccination related anaphylaxis, optimal management begins withprevention: prevaccination screening including questions about possible allergy to any component of vaccine, and anticipationof anaphylaxis by observation at least 15 minutes following vaccination are very important. The essential treatment isprompt administration of adrenaline. Since hypotension is due to a shift of fluid from intravascular to extravascular space, themainstay of treatment should be the restoration of intravascular volume. Since anaphylaxis can be biphasic administration ofcorticosteroid in preventing late phase reaction can be postulated.